Influence of Comics Media in Increasing Student Knowledge About Panu Disease at Public Alementary School 01 Sukoharjo Pati - Syaroni, Daffa; Melok Tin; Lourensya Berta Jorharlina (Herb-Medicine Journal: Terbitan Berkala Ilmiah Herbal, Kedokteran dan Kesehatan, 2025)
Pityriasis versicolor, also known as tinea versicolor, is a skin condition that is prevalent in tropical regions with high humidity levels and is brought on by an infection with the fungus Malassezia sp. To improve pupil’s knowledge of this illness, effective health education is required. The purpose of this study is to examine how comic books can be used as a teaching tool to help students at Public Alementary School 01 Sukoharjo Pati learn more about pityriasis versicolor. A quantitative experimental one group pretest-posttest design was used in this study and a stratified random selection procedure was used to choose a sample of 64 students from classes V and VI. Pretest and posttest questionnaires were used to gather data both before and after comic media instruction was given. Student’s knowledge scores significantly (p<0.05) improved after receiving comic education, we examined the data using a paired sample t-test. Student’s interest in reading and comprehending health information is also increased by the use of comic books. We found that comic books are a useful teaching tool for improving pupil’s comprehension of pityriasis versicolor. Schools and teaching staff should create more engaging and participatory health education strategies for students.